2007
DOI: 10.1002/dvdy.21156
|View full text |Cite
|
Sign up to set email alerts
|

Census of vertebrate Wnt genes: Isolation and developmental expression of Xenopus Wnt2, Wnt3, Wnt9a, Wnt9b, Wnt10a, and Wnt16

Abstract: The Wnt family of growth factors regulate many different aspects of embryonic development. Assembly of the complete mouse and human genome sequences, plus expressed sequence tag surveys have established the existence of 19 Wnt genes in mammalian genomes. However, despite the importance of model vertebrates for studies in developmental biology, the complete complement of Wnt genes has not been established for nonmammalian genomes. Using genome sequences for chicken (Gallus gallus), frog (Xenopus tropicalis), an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
78
0
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(85 citation statements)
references
References 47 publications
4
78
0
2
Order By: Relevance
“…WNT genes are involved in hair-follicle morphogenesis, 27,28 skin and tooth embryogenesis [29][30][31] and several other developmental processes. 32 It also explains that in addition to TA, hypoplastic morphological dental features, including conical tooth shapes and microdontia, occur in the permanent teeth which did develop.…”
Section: Discussionmentioning
confidence: 99%
“…WNT genes are involved in hair-follicle morphogenesis, 27,28 skin and tooth embryogenesis [29][30][31] and several other developmental processes. 32 It also explains that in addition to TA, hypoplastic morphological dental features, including conical tooth shapes and microdontia, occur in the permanent teeth which did develop.…”
Section: Discussionmentioning
confidence: 99%
“…In light of the genetic linkage between several wnt genes in other metazoans (Garriock et al 2007;Bolognesi et al 2008;Putnam et al 2008), we also looked for scaffolds containing multiple wnt genes in the three lophotrochozoan species ( fig. 2).…”
Section: Diversity Phylogeny and Genetic Linkage Of Lophotrochozoanmentioning
confidence: 99%
“…Wnt ligands are secreted glycoproteins 350-400 amino acids in length, whose domain structure is defined by the presence of 23-24 cysteines positioned at conserved sites throughout the protein's length (Nusse and Varmus 1992;Cadigan and Nusse 1997). Comparisons of available whole-genome sequences indicate that 13 wnt subfamilies were present in the common ancestor of cnidarians and bilaterally symmetric animals (Kusserow et al 2005;Croce et al 2006;Garriock et al 2007;Bolognesi et al 2008;Lengfeld et al 2009). Of these, 12 have been retained in Nematostella vectensis, a modern cnidarian, which shows one case of gene duplication, resulting in a total of 12 wnt genes (Kusserow et al 2005; note that originally two gene duplications were reported, however, our close examination indicates that wnt7a and wnt7b are splice variants of a single gene).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cerebellar vermis hypoplasia in Joubert syndrome, for example, is linked to defective canonical Wnt signaling (Lancaster et al, 2011). Wnt3 is expressed in the developing cerebellum and the dorsal spinal cord of all vertebrates (Roelink and Nusse, 1991;Bulfone et al, 1993;Garriock et al, 2007;Clements et al, 2009;Anne et al, 2013). In mice, Wnt3 is expressed prior to gastrulation and its targeted deletion causes an early developmental arrest (Liu et al, 1999).…”
Section: Introductionmentioning
confidence: 99%